2021
DOI: 10.1007/s00264-021-05263-3
|View full text |Cite
|
Sign up to set email alerts
|

Can the need for soft tissue release in total knee replacement be predicted pre-operatively? A study based on surgical navigation

Abstract: Introduction In complex and deformed knees, soft tissue release (STR) is required to obtain symmetry in the femorotibial gap. The objective of this study was to attempt to predict the need for soft tissue release using surgical navigation in total knee replacement (TKR). Methods Prospective and non-randomized study. One hundred thirty knees. At the start of navigation, an attempt was made to correct the femorotibial mechanical axis by applying force to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…Stress radiographs enable better determination, but in this study, no difference in VVD was found between those who required MNP and those who did not. Other preoperative factors which have been described include gender and BMI but our findings did not concur [2].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Stress radiographs enable better determination, but in this study, no difference in VVD was found between those who required MNP and those who did not. Other preoperative factors which have been described include gender and BMI but our findings did not concur [2].…”
Section: Discussioncontrasting
confidence: 76%
“…In the literature, preoperative deformity, whether assessed on LLRs or with computer‐assisted surgery, has been shown to predict gap asymmetry requiring soft tissue release [2, 12]. However, these studies focussed on extension gap asymmetry and did not consider flexion gap asymmetry as a separate entity.…”
Section: Discussionmentioning
confidence: 99%
“…This is a closed navigation system, that generates three-dimensional models of the femur and tibia using a bonemorphing algorithm that deforms a statistical shape model of the knee joint to match the patient's femoral and tibial bone surfaces without the need of preoperative imaging. Bone cuts were performed using manually adjusted guides, following the parameters obtained by the navigation system [33][34][35][36][37] Tracking arrays were rigidly attached to the femur and tibia. The software created the knee model based on a kinematic calculation of the centre of the femoral head and a manual mapping of the centre of knee and ankle and the joint surfaces of the femur and tibia.…”
Section: Treatment Groupsmentioning
confidence: 99%